AN ANALYSIS OF THE EFFECTS OF PERFORMANCE ON COMMUNITY SATISFACTION BASED ON CUSTOMER VOICE (CASE STUDY IN COOPERATIVE OFFICES, SMES, INDUSTRY AND TRADE, CENTRAL SUMBA DISTRICT) - Sabakula, Abner Umbu Laiya; Achmadi, Fuad; Laksmana, Dimas Indra (Journal of Sustainable Technology and Applied Science (JSTAS), 2023)
To prepare civil servants who are professional, capable of competing, and capable of anticipating rapid world developments in various aspects of life, in order to improve service quality and awareness of the need for quality human resources, various strategies that can improve employee performance must be implemented. One strategy is to provide additional employee income as a form of motivation (TPP). The goal of this study is to assess community satisfaction with the performance of the Central Sumba Regency's cooperative, SME, industry, and trade departments using Voice of Customer data. The research method employs questionnaires to assess customer satisfaction with the PDCA approach, as well as service quality and IPA analysis. The findings of this study indicate that people are dissatisfied with the performance of employees and that changes must be made. The final results obtained after using the PDCA approach and analysis using servqual and Importance Performance Analysis (IPA) are performance factors that are priority improvements and performance that must be maintained in order to meet community satisfaction. Keywords: voice of costumer, PDCA, service quality, IPA